MATURITY AND RELIGIOSITY IN SHAPING ACCOUNTING STUDENT’S PERCEPTION OF BUSINESS SCANDALS - Wiwit Apit Sulistyowati; Agung Yulianto; Acep Komara (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2022)
Business scandals involving an accountant role lead to a drop in public confidence in the business and accountant profession. This study focuses on accounting student perception of the accounting scandal based on maturity factors and religiosity. This study uses simple random sampling technique and obtained a sample number of 283 students. Respondent answers were analyzed using structural equation modelling through SmartPLS. The study results proved that maturity factors and religiosity have a positive effect on accounting student perception regarding the impact of business scandals on the accounting profession. Maturity factors positively affect accounting student perception regarding the impact of business scandals on knowledge of business scandals, while religiosity negatively affects student perceptions, but it is not significant.